Effect of C7 Modifications on Benzothiadiazine‐1, 1‐dioxide Derivatives on Their Inhibitory Activity and Selectivity toward Aldose Reductase. Issue 4 (7th November 2012) - Zhang, Shuzhen; Chen, Xin; Parveen, Shagufta; Hussain, Saghir; Yang, Yanchun; Jing, Chaojun; Zhu, Changjin
Abstract The development and progression of chronic complications in diabetic patients, such as retinopathy, nephropathy, neuropathy, cataracts, and stroke, are related to the activation and/or overexpression of aldose reductase (ALR2), which is a member of the aldo–keto reductase superfamily. A structure–activity relationship study focused on the C7 position of 1, 2, 4‐benzothiadiazine‐1, 1‐dioxide derivatives was pursued in an attempt to discover ALR2 inhibitors with enhanced potency and selectivity. These studies led to a series of new C7‐substituted compounds, which were evaluated for their inhibitory activity against ALR2; they exhibited IC50 values in the range of 2.80–45.13 nM. Two compounds with a C7‐dimethylcarbamoyl and a C7‐diethylcarbamoyl substituent, respectively, were found to be the most active and presented excellent selectivity for ALR2 over aldehyde reductase (ALR1). The structure–activity relationship analyses and molecular modeling studies presented herein highlight the importance of hydrophobic and bulky groups at the C7 position for inhibitory activity and selectivity toward ALR2.